HASIL PEMBERDAYAAN KADER-KESEHATAN-NAGARI MENGGUNAKAN APLIKASI-ANDROID UNTUK MENEMUKAN LANSIA RISIKO TINGGI STROKE TAHUN 2024 - Erdanela Setiawati (Yayasan Nusantara Hasana Berdikari, 2025)
Stroke is a non-communicable disease (NCD) that causes death and disability in Indonesia. Half of strokes occur in those over 75 years of age. More than half of the elderly in Indonesia are at high risk (RISTI) for stroke. One effective stroke prevention strategy is to focus on the RISTI population, risk factor management, and implement the use of mobile technology (Electronic Health Information Technology) in health professionals and the general public. There are no trained health cadres in efforts to prevent stroke in the elderly using mobile technology in Nagari-Gurun-Panjang-Utara. Improving the knowledge and skills of village health cadres using the android application